RANCANG BANGUN ALAT PENGUPAS KULIT TANDUK KOPI MEKANIS (Design and Construction of Coffee Bean Huller) - Annisa Fatin Amran; Achwil Putra Munir; Lukman Adlin Harahap (Universitas Sumatera Utara, 2017)
ABSTRACT The hulling of coffee bean is one of important processes in affecting the quality of green beans before roasted and grinded. The purpose of this research was to design, build, test and analyze the economic value of coffee bean huller. The parameters observed were working capacity, percentage of broken bean, percentage of unpeeled bean, percentage of bean left in huller and economic analysis. Based on this research, it was summarized that the working capacity of the equipment was 29,411 kg/hour, the percentage of broken bean was 12,534 %, the percentage of unpeeled bean was 5,3 % and the percentage of bean left in huller was 0,7 %. Economic analysis was as follows: basic costs for the first to the fifth year was Rp 400,033/kg, Rp 401,118/kg, Rp 402,284/kg, Rp 403,538/kg and Rp 404,888/kg respectively. Break even point (BEP) for the first to the fifth year was 3745,768 kg, 3951,157 kg, 4172,021 kg, 4409,455 kg and 4664,963 kg respectively. Internal rate of return (IRR) was 46,47%. Keywords: coffee, huller, machine ABSTRAK Pengupasan kulit tanduk kopi merupakan salah satu proses yang penting dalam menentukan kualitas biji kopi sebelum disangrai dan digiling. Penelitian ini bertujuan untuk merancang, membuat, menguji serta menganalisis nilai ekonomis alat pengupas kulit tanduk kopi mekanis. Parameter yang diamati yaitu kapasitas kerja alat, persentase biji pecah, persentase biji tidak terkupas, persentase biji tertinggal di dalam alat dan analisis ekonomi. Dari hasil penelitian diperoleh kapasitas kerja alat sebesar 29,411 kg/jam, persentase biji pecah sebesar 12,534 %, persentase biji tidak terkupas 5,3 %, persentase biji tertinggal di dalam alat 0,7 %. Analisis ekonomi, biaya pokok untuk tahun pertama sampai tahun kelima berturut-turut yaitu Rp 400,033/kg, Rp 401,118/kg, Rp 402,284/kg, Rp 403,538/kg dan Rp 404,888/kg. Nilai titik impas (BEP) untuk tahun pertama sampai tahun kelima sebanyak 3745,768 kg, 3951,157 kg, 4172,021 kg, 4409,455 kg dan 4664,963 kg. Internal rate of return (IRR) sebesar 46,47 %. Kata kunci: kopi, alat pengupas, mesin